Evolução da rede de drenagem na superfície de Palmas/Água Doce durante o quaternário tardio: o caso dos Córregos do Salto e Vigia - Ribeiro, Fabiano de Jesus (2016)
This dissertation studies the evolution of the drainage network of the surface of Palmas/Agua Doce during the Late Quaternary, seeking to understand the mechanisms that led to the abandonment of and palaeochannels and palaeo valley head observed in the area. For this, we proceeded to: a) a characterization of materials through the description of three stratigraphic sections, HS10, HS13 and HS 20 and the establishing of their respective transects; b) geomorphological mapping in detail scale; and c) characterization of the network of local channels and river basins related to the main waterways, Stream Do Salto and Stream Vigia. The sections HS10 and HS20 correspond to palaeochannels of 2nd order, whereas HS13 to a palaeo valley head. The stratigraphic record and its chronology indicate that the bottoms of the valleys in the study area remained active throughout the Upper Pleistocene, especially among the last interstadial and the Last Glacial Maximum, however, in the transition from the Pleistocene to the Holocene, both bottoms of low-order valleys (<4th order) as the valley head, began to act as target areas of sediment from the slopes, resulting in clogging of the valley bottoms and valley heads. The detail geomorphological mapping shows that the mapped area is divided into four geomorphological compartments: Surface 1, Surface 2, desiccated Sector Surface 2 and Surface 2 with dissection in pediments. Of these the surface 2 assumes prominence to contain abandoned paleochannels and valley heads. The characterization of the network of local channels and river basins was carried out mainly through the analysis of drainage patterns, longitudinal profiles and Basin Asymmetry Factor (FAB). The results indicated the role of the structural control influencing the dynamics of drainage channels. The integration of the results shows that events of tectonic order acted on the surface of Palmas / Agua Doce until 42,000 years AP causing blocks to rise, and the consequent expansion of the network of drainage channels, which promoted the action of erosion. From that age the network of drainage channels passes to the state of dynamic equilibrium, whose stratigraphic records indicate changes of paleohidrológicas order associated with the Last Maximum Glacia (UGM). This phase is marked by the dry season with concentrated rainfall promoting significant erosions. In the passage of the LGM to the Holocene occurs generation of colluvium responsible for clogging of canals and valley heads. To making the clogging possible, perennial channels became especially ephemeral. This fact was associated to the lowering of the water table during the LGM transition to the Holocene.